2008
DOI: 10.1002/cbic.200800085
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Mutational Analysis of the Mupirocin Gene Cluster Reveals Labile Points in the Biosynthetic Pathway: the “Leaky Hosepipe” Mechanism

Abstract: A common feature of the mupirocin and other gene clusters of the AT-less polyketide synthase (PKS) family of metabolites is the introduction of carbon branches by a gene cassette that contains a beta-hydroxy-beta-methylglutaryl CoA synthase (HMC) homologue and acyl carrier protein (ACP), ketosynthase (KS) and two crotonase superfamily homologues. In vivo studies of Pseudomonas fluorescens strains in which any of these components have been mutated reveal a common phenotype in which the two major isolable metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
5
32
0
Order By: Relevance
“…17). 150,151 Similar phenotypes were also observed for mutants in which mupS, mupQ and macpD were deleted, supporting the hypothesis that they might be involved in biosynthesis of 3-hydroxypropionate, the suspected starter unit of 9-hydroxynonanoic acid (see above). A 'leaky hosepipe' mechanism was proposed, according to which biosynthetic bottlenecks in the deletion strains lead to accumulation of intermediates on the PKS.…”
Section: Mupirocinsupporting
confidence: 72%
“…17). 150,151 Similar phenotypes were also observed for mutants in which mupS, mupQ and macpD were deleted, supporting the hypothesis that they might be involved in biosynthesis of 3-hydroxypropionate, the suspected starter unit of 9-hydroxynonanoic acid (see above). A 'leaky hosepipe' mechanism was proposed, according to which biosynthetic bottlenecks in the deletion strains lead to accumulation of intermediates on the PKS.…”
Section: Mupirocinsupporting
confidence: 72%
“…The ∆mupC/∆mupF double mutant is identical to the sin--gle mutant ∆mupC confirming that MupC acts before MupF. Interestingly, re--examination of the strain in which the KR domain (KR6) responsible for initial reduction at C7 during PKS assembly has been deleted, led to isolation of the previously reported 19 truncated product mupiric acid 13, along with the 7--keto analogues 21 and 22 of mupirocin W4 and W5. Thus a 7--hydroxyl group is clearly required for action of MmpEOR and MupW/T.…”
Section: Analysis Of Wt and Mutant Strainsmentioning
confidence: 78%
“…This phenomenon—which has, with one exception (Yu et al, 1999), not been reported for textbook ( cis -AT) PKSs—suggests the existence of an as-yet uncharacterized proofreading mechanism that releases stalled intermediates from the enzyme. Such truncated products were also observed for the rhizoxin ( 4 ) (Kusebauch et al, 2009) and, for some elongation stages, the mupirocin (Wu et al, 2008) pathways, indicating that intermediate hydrolysis is a more general phenomenon for trans -AT PKSs. Here, we report genetic, biochemical, and chemical studies of a member of the AT2 group, identifying it as a thioester hydrolase for structurally diverse N -acetylcysteamine- or ACP-bound acyl units.…”
Section: Introductionmentioning
confidence: 86%